Exploration of the Potential Relationship Between Gut Microbiota Remodeling Under the Influence of High-Protein Diet and Crohn’s Disease - Zhao, Yiming; Chen, Lulu; Chen, Liyu; Huang, Jing; Chen, Shuijiao; Yu, Zheng (Frontiers in Microbiology, 2022)
Diet and gut microbiota are both important factors in the pathogenesis of Crohn’s disease, and changes in diet can lead to alteration in gut microbiome. However, there is still insufficient exploration on interaction within the gut microbiota under high-protein diet (HPD) intervention. We analyzed the gut microbial network and marker taxa from patients with Crohn’s disease in public database (GMrepo, https://gmrepo.humangut.info) combined with investigation of the changes of composition and function of intestinal microbiome in mice fed on HPD by metagenomic sequencing. The results showed that there was an indirect negative correlation between Escherichia coli and Lachnospiraceae in patients with Crohn’s disease, and Escherichia coli was a marker for both Crohn’s disease and HPD intervention. Besides, enriched HH_1414 (one of ortholog in eggNOG) related to tryptophan metabolism was from Helicobacter, while reduced orthologs (OGs) mainly contributed by Lachnospiraceae after HPD intervention. Our research indicates that some compositional changes in gut microbiota after HPD intervention are consistent with those in patients with Crohn’s disease, providing insights into potential impact of altered gut microbes of HPD on Crohn's disease.